Model Pengelolaan Kelas Rangkap (PKR) untuk Sekolah Dasar yang Mengalami Kekurangan Guru di Daerah Perbatasan atau Terpencil di Provinsi Kalimantan Timur - MAASAWET, ELSJE THEODORA (Bioedukasi: Jurnal Pendidikan Biologi, 2015)
On the issue of distribution of teachers, for example, we have not been able to spread evenly elementary teachers in remote homeland. In fact, the number of primary school teachers as a whole are not including less. As a result, there was a shortage of teachers locally everywhere, especially in the small, difficult and remote. On the issue of disparity in quality, basil learn the average elementary school student in the big cities are generally much higher than their counterparts in remote areas. Perhaps a more appropriate blamed is because we have not found the proper techniques to perform Duplicate Classroom Management (PKR). Understanding the nature or essence of PKR, PKR is expected to no longer regard as a difficult problem to overcome. In contrast, the self will grow understanding that PKR is a definite challenge to overcome. The purpose of this study was to determine how the management class for Elementary School Teachers Experiencing Shortage of the Frontier or Remote province of East Kalimantan that occurred during this time, to find out what happened to the problem of learning patterns that have been implemented in elementary schools Experiencing Shortage Teachers in the Frontier or Remote East Kalimantan Province and develop a model to solve the problems that occurred in the study that had been conducted at the Primary School Teachers Experiencing Shortage of the Frontier or Remote Kalimantan Timur.Model development modeled after Dick & Carey with steps to identify learning objectives, learning analysis, analysis of student characteristics, formulate learning indicators, developing test items, develop learning strategies, developing and selecting materials, designing formative evaluation and revise teaching materials. Classroom management model appropriate to deal with problems in elementary Sebatik Island due to shortage of teachers is classroom management model in the sense that 221 teachers teach two classes, two subjects in the same room. This model is considered to be appropriate to the circumstances on the island of Sebatik who have never applied for duplicate classroom management model management model 221 is a model of the simplest of the three models in the management of dual class.